An Empire's New Holy Land: The Byzantine Period - Parker, S. Thomas (Near Eastern archaeology, 1999)
Here we learn of the transformation of a poor step-child into a favored daughter. The archaeology of the Byzantine Period used to be "too late" for those interested in the Biblical periods and "too early" for those scholars specialized in the remains of Islamic civilization. Now that situation has been totally transformed by a wide-ranging burst of archaeological energy involving a broad range of specialists and perspectives. In his detailed summary of the main currents and fruits of research into the material remains of Byzantine Palestine, Tom Parker begins his historical review with Diocletian to provide a more well-founded sense of the political processes that shaped the transformation of culture in the region. A summary of significant inscriptions and the implications to be drawn from the sophisticated archaeological surveys that have been accomplished in recent years leads to a review of excavations, including that new focus on smaller, rural settlements. Then the treatment shifts to the architecture, pottery and other material remains that have now been recovered, concluding with an evaluation of the impact of archaeological research on historical understandings of the period.